The Influence of Social Media on Consumptive Behavior with Lifestyle as a Mediating Variable Among Gen Z in Garut Regency - Jayanti, Amel Dwi; Susilawati, Wati; Adiatma, Dani (Golden Ratio of Mapping Idea and Literature Format, 2026)
This study aims to examine the influence of social media on consumptive behavior mediated by lifestyle among Generation Z in Garut Regency. The method used is quantitative with an explanatory design. Data for this study were obtained from questionnaires distributed online to Generation Z in Garut Regency, namely individuals born between 1997 and 2012 who actively use social media. This study used a sample of 110 respondents. Data analysis was performed using Partial Least Squares (PLS) processed through SmartPLS. It was found that social media does not directly influence consumptive behavior. However, social media can significantly influence lifestyle. Similarly, lifestyle can influence consumptive behavior. The relationship between social media and consumption behavior becomes significant when mediated by the lifestyle variable. The novelty of this research lies in the disclosure of the lifestyle mediation mechanism, which clarifies how social media can influence consumption behavior through the formation of a lifestyle that is more influenced by digital trends. The results of this study can be used to design more effective marketing strategies that are in line with the characteristics of Generation Z.